Penerapan Metode SMA Untuk Peramalan Tingkat Produksi Tanaman Pangan di Dinas Pertanian - Novita Sari Sitorus; Yessica Siagian; Romy Aulia (J-Com (Journal of Computer), 2021)
Abstract: Food is the most important foodstuff needed by humans, in addition to consumption, the production of food crops can also be used as a source of business in the economy. This study aims to predict the production of food crops in the Agriculture Office of Asahan Regency. Based on data on food crop production from 2012 to 2019 at the Asahan District Agriculture Office experienced ups and downs, food crop production sometimes does not meet the consumption of people in Asahan Regency (devisit) and sometimes overproduction (surplus). So far, the Agriculture Office of Asahan Regency has predicted the production of food crops only with estimates so that the results are not accurate. Based on these problems, a proper forecasting system is needed so that it is able to predict the production rate of food crops quickly and accurately. Applications are built using Visual Basic Net 2010 and MySQL databases and use the Single Moving Average method. The results of this study can help the Agriculture Office of Asahan Regency in predicting the amount of food crop production in the next period according to the needs. Keywords : Forecasting, Production, Food Crops, Single Moving Average  Abstrak: Pangan merupakan bahan makanan paling utama yang di butuhkan oleh manusia, selain untuk dikomsumsi, hasil produksi dari tanamana pangan juga dapat dijadikan sebagai sumber usaha dalam perekonomian. Penelitian ini bertujuan untuk melakukan prediksi produksi tanaman pangan pada Dinas Pertanian Kabupaten Asahan. Berdasarkan data produksi tanaman pangan dari tahun 2012 sampai dengan tahun 2019 pada Dinas Pertanian Kabupaten Asahan mengalami naik turun, produksi tanaman pangan terkadang tidak memenuhi konsumsi masyarakat di Kabupaten Asahan (devisit) dan terkadang kelebihan produksi (surplus). Selama ini Dinas Pertanian Kabupaten Asahan melakukan prediksi produksi tanaman pangan hanya dengan perkiraaan-perkiraan saja sehingga hasilnya tidak akurat. Berdasarkan permasalahan tersebut maka dibutuhkan sistem peramalan yang tepat sehingga mampu meramalkan tingkat produksi tanaman pangan dengan cepat dan akurat. Aplikasi dibangun menggunakan Visual Basic Net 2010 dan database MySQL serta menggunakan metode Single Moving Average. Hasil dari penelitian ini dapat membantu Dinas Pertanian Kabupaten Asahan dalam memprediksi jumlah produksi tanaman pangan pada periode berikutnya sesuai dengan kebutuhan. Kata Kunci : Peramalan, Produksi, Tanaman Pangan, Single Moving Average